Enhancing Students’ Ability in Composing a Well-Developed Paragraph through Social Constructive Learning Facilitated by Peer-Assessment - Susilowati, Tintin; Fachriza, Aries (Institut Agama Islam Negeri Ponorogo, 2024)
A social constructive learning refers to a context used to build a collaborative learning atmosphere to have in-depth learning by empowering students’ performances and progress cooperatively. It is needed to upgrade students’ proficiency in delivering an idea through a written expression. Therefore, the students can build up their writing ability constructively. This is a descriptive qualitative study that is used to explore a meaningful learning experience in a paragraph writing class using peer-assessment. This research involved 23 students at the second semester of the English department of State Islamic Study of Ponorogo. The data were gathered from a performance test of all the participants, supported by the data derived from interviews, and documentation was also conducted to support the data of the students’ ability in writing. The data were analyzed interactively through (1) data reduction; (2) data display; and (3) conclusion. The results of the study showed that the students were triggered to rearrange their writing confidently because their peers showed their weaknesses and gave suggestions on their mistakes. It boosted the students to write better, so that, the students could produce the expected paragraph writing outcome after they were actively upgrading performances in writing through ongoing learning. Hence, the students were directed to elaborate their writing ability through interactive, constructive, and reflective activities. This paper was aimed at describing the implementation of social constructive learning in a paragraph writing class mediated by the use of peer-assessment. The implication of this study is to promote the students to learn paragraph writing faster since this learning triggered the students have experiences in learning together by checking, sharing, solving, and formulating a solution.